2023
DOI: 10.1161/circresaha.122.320781
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Fap Promotes Cardiac Repair by Stabilizing BNP

Abstract: RATIONALE: Myocardial infarction (MI) elicits cardiac fibroblast activation and ECM (extracellular matrix) deposition to maintain the structural integrity of the heart. Recent studies demonstrate that Fap (fibroblast activation protein)—a prolyl-specific serine protease—is an important marker of activated cardiac fibroblasts after MI. OBJECTIVE: This study aims to test whether Fap is a critical regulator of cardiac repair after MI and to uncover the und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 39 publications
4
11
0
Order By: Relevance
“…Therefore, our findings show that during the acute phase of HF, plasma FAP levels are decreased. Our results are in line with those of Sun Y et al, who observed in acute myocardial infarction that tissue levels of FAP were overexpressed while plasma FAP levels were decreased [ 13 ]. However, there is no explanation for this paradoxical reduction in plasma FAP levels.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, our findings show that during the acute phase of HF, plasma FAP levels are decreased. Our results are in line with those of Sun Y et al, who observed in acute myocardial infarction that tissue levels of FAP were overexpressed while plasma FAP levels were decreased [ 13 ]. However, there is no explanation for this paradoxical reduction in plasma FAP levels.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, Sun Y et al, observed in ischemic HF that tissue levels of FAP were overexpressed while plasma FAP levels were decreased [ 13 ]. Despite having been studied, little is known about this paradoxical reduction in plasma FAP levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is only expressed at low levels in most normal adult mice or human tissues. 76,79 Several research showed that FAP expression plays vital roles in immunosuppression, 80 pro-angiogenesis, 81 and intracellular signaling regulation. 82 FAP has also demonstrated dipeptidyl-and endo-peptidase activity.…”
Section: Target Fibroblast Activation Protein (Fap) With Car-t Cellsmentioning
confidence: 99%
“…Further, among non-oncological diseases, FAP expression has been reported in idiopathic pulmonary fibrosis, autoimmune diseases, liver cirrhosis, myocardial infarction, and atherosclerosis [6]. Sun et al [10] reported that in mice, the inhibition of FAP expression improves cardiac function following myocardial infarction and prevents the overactivation of fibroblasts, thereby limiting scar formation. Therefore, FAP is an important target in the pathophysiology, diagnosis, and treatment of cancers and fibrotic diseases.…”
Section: Introductionmentioning
confidence: 99%